Development of measures to improve the quality of personnel management functions - Saktaganova , G.S. (BUKETOV BUSINESS REVIEW, 2017)
At the present stage structural changes in economy and rapid development of science and technology led to increase of a human factor role in production and management. It is quite natural that at each entity there is a necessity for determination of number of personnel, for effective system of matching, hiring and placement of personnel, for providing their occupation inclusive of production interests and the worker`s interests ,in system of compensation for work, in considering of individual problems of workers, improvement of their social conditions and vacation. Improving the efficiency of personnel management can be achieved by using the following factors: improvement of labor organization; involving personnel in process control; training and development of staff through systematic training and improvement of qualification of workers. In the article are given recommendations about forming and development of an effective personnel management system on the example of ENU of L.N. Gumilev on the basis of application of methods of material and moral incentives, are offered actions for increase an effectiveness of personnel management in organization. Are given expected results from implementation of complex actions for increase effectiveness of personnel management system. In general, the expected results, the implementation of the recommendations and measures to improve the functions of personnel management will improve the quality of HR functions that contribute to the revitalization of the work of staff, as well as the formation and development of an effective system of personnel management. The expected results include: improvement of quality of work of personnel; increase in prestigiousness of the entity and forming of motivation of revenues to work; forming of trust to the entity in general and to workers in particular; forming of the corporate philosophy and corporate ethics of the entity based on mutual assistance, creativity and self-realization of each worker.